Amalan Etika Kerja Dalam Perkhidmatan Awam Malaysia : Satu Kajian di Kementerian Pembangunan Usahawan dan Koperasi Malaysia - Mohd. Ribuan, Che Omar (2004)
The objectives of this study is to determine the level of work ethic among the employees of the Ministry of Entrepreneur and Cooperative Development (MECD) and also to determine whether there are significant difference in work ethic characteristics among the MECD employees based on demographic variables namely gender, age, marital status and educational level as well as work variables namely job category, income and tenure of service. This study was conducted on a sample of 187 MECD employees using a 73-item questionnaire to measure all 12 pillars of The Twelve Pillars Work Ethic. T-test, one-way ANOVA test and Post HOC Tukey HSD test were used in the analysis to test whether there are significant difference in work ethic characteristics based on demographic and work variables among the MECD employees. The empirical results indicate that the level of work ethic among the MECD employees are good with a mean score of 3.89. Results further reveal that MECD work ethic characteristics differs significantly across gender, age, educational level, job category, income and tenure of service whereas there is no difference based on marital status. The findings have theoritical implications towards a better understanding of the relationship between demographic variables as well as work variables and work ethic. It is also hope that the findings of this study could assist the MECD management formulate sound strategies to improve the present programs and to implement new programs towards enhancing the work ethic of MECD employees.